A influência da música na experiência de compra em marketplaces - Cordeiro, Caio Daher Moura Campello (2023)
E-commerce has been growing more and more, both in Brazil and in the world, also increasing competitiveness in the marketplace market. An alternative to stand out from the competition is to create a shopping environment capable of innovating and improving the user experience. With that in mind, this research aims to use music related to the musical taste of each researched person in order to understand how and if musical stimuli can contribute to the user experience at the time of purchase in order to validate the hypothesis that these stimuli can result in positive effects on the consumer experience. This is descriptive research that will utilize a survey with open-ended questions to modulate a test with an experiment simulating a purchasing experience. The survey involved 187 respondents and collected demographic data, purchasing behavior data, and insights from the respondents regarding the integration of music in virtual shopping environments. The experiment included 10 participants who engaged in a purchasing simulation while listening to playlists featuring music selected according to their musical preferences. At the end of the experiment, they completed a questionnaire aimed at sharing their experience, which was quantified using the Likert scale and semantic differential scale to measure the quality of the experience and the impact of the music on it. The results showed that the addition of music connected to the consumer's personal taste improved the experience, making it more relaxing, focused and enjoyable